Presence of neutralizing antibodies to Orthopoxvirus in Capybaras (Hydrochoerus hydrochaeris) in Brazil - André Victor Barbosa; Maria Luiza G Medaglia; Herbert S Soares; Jociane C Quixabeira-Santos; Solange M Gennari; Clarissa R Damaso (Journal of Infection in Developing Countries)
Cantagalo virus is a strain of vaccinia virus (genus Orthopoxvirus) and the etiological agent of an important vesicopustular disease that affects dairy cows and milkers in Brazil. The reservoirs involved in the maintenance of this virus in nature are unknown. In the present work, the detection of neutralizing antibodies to Orthopoxvirus in capybaras collected in São Paulo state is reported. Capybaras are the largest rodent species native to South America and have already been reported as putative reservoirs of other pathogenic microorganisms. Thirteen out of thirty-three serum samples were found positive in plaque-reduction neutralization tests, some of them showing high titers compared to positive controls. These results suggest that capybaras may play a role in the infection cycle of vaccinia virus in Brazil.